Reading Self-Efficacy and Reading Comprehension: A Correlational Study Among Freshmen: Penelitian - Resfiana Irani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Reading is an important skill for university students, particularly in English Language Education study program since academic texts are mostly written in English. However, freshmen come from diverse educational backgrounds, which might influence their reading abilities and confidence in handling academic texts. One psychological factor that connected to students’ reading performance is reading self-efficacy. The aim of this study is to examine the correlation between reading self-efficacy and reading comprehension among freshmen at Universitas Negeri Surabaya. Quantitative approach using descriptive statistic and correlational design was used in study The participants were 239 freshmen gathered through total sampling. The data were gathered using reading self-efficacy questionnaire adapted from the previous study and students’ reading comprehension score from the Test of Proficiency (TEP). The data collected were analyzed using descriptive statistics and Pearson Product Moment correlation through SPSS 27. The result of the study indicated that most students have a moderate level of reading self-efficacy and achieved reading comprehension at B1 (intermediate) level based on the CEFR classification. However, the correlation analysis showed no statistically significant relationship between reading self-efficacy and reading comprehension (p>0.05)